2011
DOI: 10.1111/j.1399-3054.2011.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Net cadmium flux and accumulation reveal tissue‐specific oxidative stress and detoxification in Populus × canescens

Abstract: To characterize the dynamics of Cd²⁺ flux in the rhizosphere and to study cadmium (Cd) plant-internal partitioning in roots, wood, bark and leaves in relation to energy metabolism, reactive oxygen species (ROS) formation and antioxidants, Populus × canescens plantlets were exposed to either 0 or 50 µM CdSO₄ for up to 20 days in the nutrient solution. A strong net Cd²⁺ influx in root apex was observed after Cd exposure for 24 h, even if net Cd²⁺ influx decreased gradually in roots. A large amount of Cd was accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
118
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(127 citation statements)
references
References 54 publications
7
118
0
2
Order By: Relevance
“…Li et al (2011b) reported SOD and CAT activity decreased when wheat seedlings (Triticum aestivum L. Yangline 15) were exposed to Cd, as compared to control plants. He et al (2011) found antioxidant enzymes (SOD, POD, CAT) in Populus  canescens were influenced by Cd exposure time and tissue (root, wood, bark, leaf). He et al (2013b) indicated the activity of antioxidant enzymes (SOD, POD, CAT) in Populus  canescens were unchanged or reduced under Cd stress.…”
Section: Antioxidant Enzymesmentioning
confidence: 90%
“…Li et al (2011b) reported SOD and CAT activity decreased when wheat seedlings (Triticum aestivum L. Yangline 15) were exposed to Cd, as compared to control plants. He et al (2011) found antioxidant enzymes (SOD, POD, CAT) in Populus  canescens were influenced by Cd exposure time and tissue (root, wood, bark, leaf). He et al (2013b) indicated the activity of antioxidant enzymes (SOD, POD, CAT) in Populus  canescens were unchanged or reduced under Cd stress.…”
Section: Antioxidant Enzymesmentioning
confidence: 90%
“…Net fluxes of these ions were measured noninvasively using a scanning ion-selective electrode technique (SIET system, BIOeIMeXY, Younger USA Science and Technology Corp. MA, USA). A detailed description of the method has been presented elsewhere (Xu et al, 2006;Li et al, 2010;He et al, 2011). The ionselective microelectrode with 2e4 mm aperture and the oxygenmicroelectrode were manufactured and silanized by Xuyue (Beijing) Sci.…”
Section: Determination Of Root Morphology and Physiologymentioning
confidence: 99%
“…Although Cd entry to root cells is the first key process for phytoremediation, only several reports have currently described the dynamics of Cd 2 þ flux along root surface by employment of ion-selective microelectrodes (He et al, 2011;Farrell et al, 2005;Pineros et al, 1998). Up to now, little is known about the dynamics of Cd 2 þ flux in the rhizosphere of halophytes plants.…”
Section: Introductionmentioning
confidence: 99%